Enantioselective Discrimination of Histidine by Means of an Achiral Cubane-Bridged Bis-Porphyrin - Senge, Mathias (My University, 2021)
A Langmuir film of cubane-bridged bisporphyrin (H2por-cubane-H2por) at the air/water interface was developed and characterized. The floating film was successfully employed for the chiral discrimination between l- and d-histidine. The enantioselective behavior persisted after the deposition of the film on a solid support using the Langmuir-Schaefer method. Distinct absorption and reflection spectra were observed in the presence of l- or d-histidine, revealing that conformational switching was governed by the interaction between H2por-cubane-H2por and the histidine enantiomer. The mechanism of chiral selection was investigated using an ad hoc modified nulling ellipsometer, indicating the anti-conformation was dominant in the presence of l-histidine, whereas the presence of d-histidine promoted the formation of tweezer conformation.
Keywords: Langmuir film; chiral discrimination; floating film